2015
DOI: 10.1111/ejn.13029
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of temporo‐occipital activity by frontal oscillations during virtual mirror exposure causes erroneous self‐recognition

Abstract: Self-face recognition, a hallmark of self-awareness, depends on 'off-line' stored information about one's face and 'on-line' multisensory-motor face-related cues. The brain mechanisms of how on-line sensory-motor processes affect off-line neural self-face representations are unknown. This study used 3D virtual reality to create a 'virtual mirror' in which participants saw an avatar's face moving synchronously with their own face movements. Electroencephalographic (EEG) analysis during virtual mirror exposure r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 64 publications
4
39
2
Order By: Relevance
“…Pineda, 2005;Rizzolatti et al, 2001) and has been associated with greater sense of agency (e.g. Serino et al, 2015). However, there is some support for their findings as Our results demonstrated -suppression during both egocentric and allocentric movements, however, after tACS we only observed reduced -suppression during observation of egocentric movements.…”
Section: Involvement Of  In Processing Of Allocentric Hands Movementcontrasting
confidence: 49%
See 1 more Smart Citation
“…Pineda, 2005;Rizzolatti et al, 2001) and has been associated with greater sense of agency (e.g. Serino et al, 2015). However, there is some support for their findings as Our results demonstrated -suppression during both egocentric and allocentric movements, however, after tACS we only observed reduced -suppression during observation of egocentric movements.…”
Section: Involvement Of  In Processing Of Allocentric Hands Movementcontrasting
confidence: 49%
“…One may also question whether observation of a movement from the egocentric perspective can be perceived as belonging to the self more than to others. It has been demonstrated that observation of a virtual morphed face can be processed and perceived as more similar to one's own face if it moves in synchrony with the observer's self-initiated movements (Serino et al, 2015). It is assumed that this effect is due to matching between predicted proprioceptive and somatosensory consequences of executed movements and visual feedback.…”
Section: Involvement Of  In Processing Of Allocentric Hands Movementmentioning
confidence: 99%
“…After seeing the image of avatars with different phenotypes, subjects revealed a greater self-identification with more diverse phenotypic characteristics. Using enfacement illusions with EEG measurements, Serino et al (2015) observed activation of face-specific regions correlating to the increased identification with the avatar's face.…”
Section: Using Perceptual Illusions To Promote Empathy-related Abilitiesmentioning
confidence: 99%
“…As shown by Serino et al. () with adults, the use of virtual mirror setups could disentangle the respective contribution of visual, tactile, and proprioceptive signals in the development of mirror self‐recognition, as well as the distinction between self and others.…”
Section: Discussionmentioning
confidence: 95%